2020
DOI: 10.1186/s12868-020-0551-3
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid ameliorates depression-like behaviour in a rat model of chronic unpredictable mild stress

Abstract: Background: Depression is characterized by significant and low mood. Classical antidepressants are still not adequate in treating depression because of undesirable side effects. Folic acid, a member of the vitamin B complex, in considered to be strongly associated with the function and development of the central nervous system. Thus, in this study, we established a model of depression through chronic unpredictable mild stress (CUMS) in rats and assessed the antidepressant effects and mechanisms of folic acid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Although the specific pathophysiological mechanisms underlying depression are not yet completely clear, animal and human studies have illustrated that dysfunctional intracerebral neurotransmission, such as 5-HT, NE, and DA, is positively associated with the development of depression. 80 In the current study, CUMS exposure disrupted cholinergic and monoaminergic transmission, as demonstrated by reduced hippocampal levels of AChE, 5-HT, DA and NE, which was associated with increased MAO activity. A previous report showed that the hyperactivity of the HPA axis is correlated with a reduction in 5-HT and NE levels in brain tissue.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although the specific pathophysiological mechanisms underlying depression are not yet completely clear, animal and human studies have illustrated that dysfunctional intracerebral neurotransmission, such as 5-HT, NE, and DA, is positively associated with the development of depression. 80 In the current study, CUMS exposure disrupted cholinergic and monoaminergic transmission, as demonstrated by reduced hippocampal levels of AChE, 5-HT, DA and NE, which was associated with increased MAO activity. A previous report showed that the hyperactivity of the HPA axis is correlated with a reduction in 5-HT and NE levels in brain tissue.…”
Section: Discussionmentioning
confidence: 48%
“…Earlier studies have reported increased levels of pro-inflammatory cytokines in the prefrontal cortex of animal models of depression. 4 , 59 , 80 The inflammatory response that follows CUMS exposure has been suggested to be associated with enhanced COX-2/PGE2-driven inflammatory pathways and the increased activation of NF-κB, leading to increased pro-inflammatory cytokines production. 81 , 82 By contrast, the administration of Se nanoformulations exhibited neuroprotective activity via the suppression of the inflammatory cascade in epileptic mice and diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this study provides the important data for later time points (such as Day 14) to support restoration of LCBF and sustainable positive outcomes. NBP was long recognized as a neuroprotective drug in acute and chronic conditions [ 48 , 49 ]. The mechanistic reason for focusing on the possible association of NBP and collateral circulation was based on the roles of NBP in robust regulation of several vascular regenerative factors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coherently with its hypoglycemic effect, NGF efficiently ameliorates the molecular alterations reminiscent of insulin resistance in basal forebrain cholinergic neurons [ 89 ]. In addition, NGF administration counteracts ER stress and apoptosis observed in Schwann cells during diabetic peripheral neuropathy, and efficiently attenuates neuronal death under glucose fluctuation in diabetic encephalopathy [ 90 , 91 ]. In contrast to BDNF and NGF, very little experimental evidence highlights the involvement of NT-3 or NT-4 in the regulation of energy homeostasis.…”
Section: Neurotrophins: From Cell Signaling To Metabolic Processesmentioning
confidence: 99%